Star wars trilogy : bonus material [videorecording (DVD)] - Lucas, George, 1944- (Star wars trilogy., 2004)
Go behind the scenes, and experience the journey from the earliest versions of the script to the blockbuster debut of the films that changed the face of cinema. Explore the creation of the Star Wars films, the development of the classic characters, and the birth of the lightsaber, through documentaries, featurettes, interviews, rare footage, theatrical trailers, stills collections, poster art, and more. Includes the story of the making of all the Star Wars films: documentary and features, video games, still galleries, trailers, TV spots, Episode III preview (The Return of Darth Vader) and more.